Analisis Rasio Keuangan untuk Mengukur Kinerja Keuangan Perusahaan Manufaktur pada Sektor Kimia di Indonesia Tahun 2019-2023 - Siti Nurul Hidayati; Putri Rahayu; Diana Indah Sri Lestari P. A; Cholis Hidayati (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This research aims to evaluates a financial performance at PT Alkindo Naratama Tbk, PT Toba Pulp Lestari Tbk, and PT Tjiwi Kimia Paper Mill Tbk in the Indonesian chemical manufacturing industry for the 2019–2023 period using descriptive methodologies and a qualitative approach. In addition to other sources like articles and journals, secondary data was collected from the financial and annual reports of businesses listed on the Indonesia Stock Exchange (IDX). The results of the analysis show that PT Alkindo Naratama Tbk has excellent liquidity and operational efficiency, indicating the company's ability to meet short-term obligations and practice prudent asset management. The most successful business, as determined by ROA and ROE, is PT Toba Pulp Lestari Tbk, which makes efficient use of equity and assets. With the highest dividend and the lowest debt-to-asset ratio, PT Pabrik Kertas Tjiwi Kimia Tbk stands out in terms of funding stability and offers investors alluring rewards. In order to increase the competitiveness of Indonesia's chemical manufacturing industry, managers, investors, and policymakers should utilize this study's summary of financial performance as a strategic guide.